2015
DOI: 10.1080/01496395.2015.1009115
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for xylitol purification and crystallization: A Review

Abstract: This paper reviews the literature on the main aspects of purification and crystallization of xylitol produced either by chemical or biotechnological routes. Different strategies have been used to clarify media containing xylitol: activated charcoal, pH adjustment, ion-exchange resins, membrane separation, chromatographic methods, liquid-liquid extraction and precipitation, or a combination of these techniques. This study explores the most recent results of research-work carried out in this field as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 32 publications
2
29
0
10
Order By: Relevance
“…Another challenge in the xylitol fermentation process is its recovery from the broth. Few studies related to xylitol recovery are reported . Generally, in bioprocesses, recovery and purification are complicated steps that interfere in the final cost of the bioproduct .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another challenge in the xylitol fermentation process is its recovery from the broth. Few studies related to xylitol recovery are reported . Generally, in bioprocesses, recovery and purification are complicated steps that interfere in the final cost of the bioproduct .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, in bioprocesses, recovery and purification are complicated steps that interfere in the final cost of the bioproduct . Most of the published studies describe crystallization methods for the recovery of xylitol from fermented broth (with hemicellulosic hydrolysates of hardwood, corn cobs, sugarcane bagasse, and synthetic mediums) with a yield between 40% and 60% and purity less than 98% . However, non‐conventional recovery technologies, such as supercritical fluid extraction, are being evaluated for different applications in biorefineries …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Xylitol could also be commercially obtained chemically by using catalyst, 4 or biotechnologically by using fungi, bacteria or yeast. 5 The separation performance of xylitol is a complicated process due to presence of impurities and this separation can be achieved by using different techniques such as: (1) crystallisation (75%), 6 (2) adsorption (60%), 7 or (3) membrane technology (82%). 8,9 Based on this, membrane technique is reported to have given the highest purity compared to others.…”
Section: Introductionmentioning
confidence: 99%